A New Large-scale Pre-purification for Peroxidase from Plant Cell Cultures - Pyo, Sang-Hyun; Hong, Seung-Suh; Kim, Jin-Hyun (The Korean Society for Biotechnology and Bioengineering, 2000)
A novel pre-purification method was developed for producing peroxidase to guarantee high purity and yield from plant cell cultures in large-scale process. This method was a simple and efficient procedure for the isolation and pre-purification of peroxidase from the biomass consisting of active clay treatment, followed by cationic exchange chromatography. The use of active clay in the pre-purification process allows for rapid and efficient separation of peroxidase from interfering compounds and dramatically increases yield and purity of crude peroxidase for purification steps compared to alternative processes. This pre-purification process serves to minimize the buffer usage, size and complexity of the HPLC operations for peroxidase purification. This process is readily scalable to a pilot plant and eventually to a production environment where mass production of material are expected to be produced.